Acute pancreatitis as an adverse event in patients with the duodenal-jejunal bypass liner - Betzel, Bark; Homan, Jens; Aarts, Edo; Janssen, Ignace; Spanier, Marcel; Wahab, Peter; Groenen, Marcel; Berends, Frits (Endoscopy, 2015)
Placement of the duodenal-jejunal bypass liner (DJBL) is a minimally invasive technique for the management of patients with type 2 diabetes mellitus and obesity. Acute pancreatitis was seen in 5 of 167 patients (3 %) in our series. It is suggested that acute pancreatitis in patients with the DJBL results from either direct blockage or edema of the major duodenal papilla, which may be caused by the following: migration of the anchor of the DJBL, accumulation of food debris between the liner and the duodenal wall, or reflux of duodenal contents into the pancreatic duct due to intraluminal hypertension caused by the liner. Early removal of the DJBL resulted in fast and complete recovery, whereas delayed diagnosis and removal led to severe, necrotizing acute pancreatitis.